Principles of data management : facilitating information sharing - Gordon, Keith (BCS Learning & Development Limited, 2013)
Data is a valuable corporate asset and its effective management can be vital to success. This professional guide covers all the key areas of data management, including database development and corporate data modelling. The new edition covers web technology and its relation to databases and includes material on the management of master data.